Ẓafaralmuḥaṣṣilīn bāḥvāl almuṣannifīn : maʻ Qaratulʻayūn fī taẕkiratulfunūn . - Gangohī, Muḥammad Ḥanīf, 1935- (Ḥanīf Bukḍipo, 1970)
On the bona fide Hadith (Islamic traditions); includes biographies of compilers.